Managerial Factors Influence and Customer Relationship Management of Competitive Advantage for Improving Performance in Transportation and Logistics in Semarang - Hanifati, Kinanti; Perdhana, Mirwan Surya (Budapest International Research and Critics University, 2022)
This study discusses the influence of managerial factors and customer relationship management toward competitive advantage to increase performance in transportation and logistics service companies in Semarang. Total sample in this research is 127 companies. Collecting data using a questionnaire, an analyzed data tool which has been used is Structural Equation Modeling (SEM) through the AMOS 24.0 program. The result of data analyzed showed that the research model can be accepted with goodness of fit, they are chi-square = 145.188; probability= 0.156; GFI= 0.893; AGFI= 0.858; TLI= 0.985; CFI= 0.988; CMIN/DF= 1.125; and RMSEA = 0.032. All hypotheses can be accepted after SEM analysis is conducted. This matter means that managerial factors and customer relationship management have a positive effect and are significant toward competitive advantage. Then competitive advantage has a positive effect and is significant toward company performance.